Concomitant diagnosis of Trypanosoma cruzi and HIV in a patient with neurologic manifestations: A case report - Emmanuel Molina Solano; Mauricio Mora Díaz; Stephanie Montoya Madriz; Mauricio Lizano Calvo; Lissette Retana Moreira (Brazilian Journal of Infectious Diseases)
American trypanosomiasis or Chagas disease is a vector-borne infection caused by the protozoan parasite Trypanosoma cruzi, characterized by acute and chronic phases; reactivations due to immunosuppression can occur. In this case report, we confirm the presence of trypomastigotes of T. cruzi in a patient with neurologic manifestations. For this purpose, a battery of techniques, including direct examination of cerebrospinal fluid, Giemsa stains, sample cultures, serology and molecular techniques were employed. The patient was treated with nifurtimox for 6 months and started antiretroviral therapy as the concomitant diagnosis of HIV was also performed, showing no sequelae nor adverse effects. A follow-up of the patient´s health status was performed for 42 months.